Mussaenda recurvata (Rubiaceae), a new species from southern Vietnam with observations on its heterostyly - Naiki, Akiyo; Tagane, Shuichiro; Toyama, Hironori; Dang, van Son; Yahara, Tetsukazu (Phytotaxa, 2017)
Herein, Mussaenda recurvata, a new species from Hon Ba Nature Reserve, southern Vietnam, is described and illustrated. This species is morphologically similar to M. longipetala, distributed from southern China to northern Vietnam, in having recurved stipules and densely pilose and puberulent hairs throughout, but differs in its strongly recurved calyx lobes, a shorter corolla tube, and ovate corolla lobes. The species is morphologically heterostylous and it appears to be functionally dioecious. An updated key to Mussaenda species in Vietnam, Laos, and Cambodia is also provided.